Pelatihan Pemanfaatan Teknologi Informasi dalam Pembelajaran di Sekolah Dasar pada Masa Pandemi Covid-19 di Kelurahan Cigadung, Kuningan - Lismaya, Lilis; Eliyanti, Marlina; Nurhasanah, Aan (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2021)
The community service that we designed aims to improve the skills of applying science and technology in the community, especially the use of Information Technology in learning in elementary schools during the covid-19 pandemic. The target of this service is generally elementary school students and teachers in Cigadung Village. The method or performance of community service to achieve these goals is the implementation of Information Technology training through the introduction of computer hardware and software components, steps to create a gmail email, steps to use google classroom, google meet, zoom and how to draw using Ms.Paint. The implementation of the activities includes two elementary schools and 1 MD in the Cigadung village. The main activity is that participants take part in training to carry out direct practice using a computer/laptop/android with various activities in it to help students and teachers in an effort to optimize learning activities during online learning during the covid-19 pandemic. Keyword : Training, Information Technology, Learning, Elementary School, Covid-19.